1976
DOI: 10.1001/archneur.1976.00500090062012
|View full text |Cite
|
Sign up to set email alerts
|

Serum Dopamine- -Hydroxylase Activity in Migraine

Abstract: Serum dopamine-beta-hydroxylase (DBH) activity was measured during headache-free intervals in 17 patients with migraine and during the headache interval in 16 patients with muscle contraction headache, as well as in 40 normal subjects. The DBH activity was significantly higher in the migraine patients (46.5+/4.5 units) than in the controls (24.9+/2.4 units), whereas no significant difference was observed between the patients with muscle contraction headache (29.4+/4.5 units) and the controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 8 publications
0
33
0
Order By: Relevance
“…Takeshima et al [38] reported the same conclusion after measuring plasma platelet factor 4 and platelet NA in patients with MwoA and MwA in basal conditions and during the cold-pressor test. Other authors [34,39] found an increase in dopamine β-hydroxylase activity in venous blood of migraineurs during and between attacks and suggested a sympathetic hyperfunction. Urinary excretion of vanillymandelic acid, a reliable index of sympathetic activity, has been found both increased [40] and normal [41] during migraine attacks.…”
Section: Biochemical Studiesmentioning
confidence: 91%
“…Takeshima et al [38] reported the same conclusion after measuring plasma platelet factor 4 and platelet NA in patients with MwoA and MwA in basal conditions and during the cold-pressor test. Other authors [34,39] found an increase in dopamine β-hydroxylase activity in venous blood of migraineurs during and between attacks and suggested a sympathetic hyperfunction. Urinary excretion of vanillymandelic acid, a reliable index of sympathetic activity, has been found both increased [40] and normal [41] during migraine attacks.…”
Section: Biochemical Studiesmentioning
confidence: 91%
“…Octopamine in the elute was converted to p-hydroxybenzaldehyde by addition of 0.2 ml of 2% NaIO 4 . Excess periodate was reduced by addition of 0.2 ml of 10% NaS 2 O 6 .…”
Section: Methodsmentioning
confidence: 99%
“…The mean activity of serum DBH in 40 healthy subjects measured by this method in our hands was 24.9 ± 2.4 units (range 2 to 64). 6 Total serum protein was determined by the method of Lowry et al 13 Fig. 1 illustrates typical changes in serum DBH and creatine phosphokinase (CPK) activity (normal range 0-12 units/ml), total serum protein and the blood pressure of a 68-year-old male patient with cerebral hemorrhage.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations